Phase 1b clinical trial of pucotenlimab (HX008), a novel anti-PD-1 monoclonal antibody, combined with gemcitabine and cisplatin in the first-line treatment of metastatic triple-negative breast cancer - Cao, Jun; Wang, Biyun; Zhang, Jian; Tao, Zhonghua; Wang, Leiping; Hu, Xichun (Frontiers in Oncology, 2022)
Background Pucotenlimab, also called HX008, is a humanized anti-PD-1 antagonist IgG4 mAb. It blocks programmed cell death protein 1 (PD-1), programmed-death ligand 1 (PD-L1), and programmed death ligand-2 (PD-L2). In the CBCSG 006 trial, gemcitabine plus cisplatin (GP) has shown impressive antitumor activity as first-line therapy for metastatic triple-negative breast cancer (mTNBC). The phase 1b study was conducted to assess the safety and preliminary antitumor activity of pucotenlimab when combined with GP in patients with mTNBC in the first-line setting. Methods Eligible patients with mTNBC with ≥6 months of DFI (disease-free interval) who have never received antitumor therapy for metastatic disease were screened. Participants received pucotenlimab at 3 mg/kg (d1, q3w) plus gemcitabine at 1,250 mg/m2 (d1, 8, q3w) and cisplatin at 75 mg/m2 (d1, q3w). Eligible patients received up to six cycles of pucotenlimab along with GP chemotherapy, while pucotenlimab could be maintained until disease progression or unacceptable toxicity occurred or withdrawal of informed consent. This study was registered in China under registration number CTR20191353. Results Between July 2019 and March 2020, 31 patients were enrolled in this study. The median age was 50 (range 28–68) years. Among 31 patients who were evaluated, 25 (80.6%) experienced objective response and the other six (19.4%) experienced stable disease (SD). As of 4 August, the median progression-free survival (PFS) was 9.0 months (95% CI, 6.2–9.2). The most common grade 3 or 4 treatment-related adverse events included neutropenia (74.1%), anemia (35.5%), thrombocytopenia (32.3%), hypocalcemia (9.7%), hypokalemia (9.7%), and alanine aminotransferase increased (6.5%). There were no treatment-related deaths. Conclusion Pucotenlimab plus GP demonstrated promising activity and a manageable safety profile in patients with mTNBC in the first-line setting.